Cistanche tubulosa Phenylethanoid Glycosides Induce Apoptosis of Hepatocellular Carcinoma Cells by Mitochondria-Dependent and MAPK Pathways and Enhance Antitumor Effect through Combination with Cisplatin. (May 2021) - Yuan, Pengfei; Fu, Changshuang; Yang, Yi; Adila, Aipire; Zhou, Fangfang; Wei, Xianxian; Wang, Weilan; Lv, Jie; Li, Yijie; Xia, Lijie; Li, Jinyao
Cistanche tubulosa is a type of Chinese herbal medicine and exerts various biological functions. Previous studies have been demonstrated that Cistanche tubulosa phenylethanoid glycosides (CTPG) exhibit antitumor effects on a variety of tumor cells. However, the antitumor effects of CTPG on HepG2 and BEL-7404 hepatocellular carcinoma (HCC) cells are still elusive. Our study showed that CTPG significantly inhibited the growth of HepG2 and BEL-7404 cells through the induction of cell cycle arrest and apoptosis, which was associated with the activation of MAPK pathways characterized by the up-regulated phosphorylation of p38, JNK, and ERK1/2 and mitochondria-dependent pathway characterized by the reduction of mitochondrial membrane potential. The release of cytochrome c and the cleavage of caspase-3, -7, -9, and PARP were subsequently increased by CTPG treatment. Moreover, CTPG significantly suppressed the migration of HepG2 through reducing the levels of matrix metalloproteinase-2 and vascular endothelial growth factor. Interestingly, CTPG not only enhanced the proliferation of splenocytes but also reduced the apoptosis of splenocytes induced by cisplatin. In H22 tumor mouse model, CTPG combined with cisplatin further inhibited the growth of H22 cells and reduced the side effects of cisplatin. Taken together, CTPG inhibited the growth of HCC through direct antitumor effect and indirect immunoenhancement effect, and improved the antitumor efficacy of cisplatin.